Pengaruh Keuangan, Literasi, Gaya Hidup, dan Kemampuan Akademik Terhadap Perilaku Mahasiswa dalam Mengelola Keuangan - Elvani Malihatus Salka; Yudas Tadius Andi Candra (PT Bone Jaya Kreatif, 2024)
The topic of financial behavior is a common subject of conversation these days, particularly concerning society's spending habits. In Indonesia, the limited proficiency in financial management has led individuals to indulge in their wants, resulting in a heightened level of consumption. This consumption-focused lifestyle is not only seen in the general public, but also includes students. The increase in consumptive behavior among students and the younger generation in recent years has made financial management more complex. The aim of this study was to ascertain the impact of financial literacy, lifestyle, and academic ability on the financial management behavior of Mercu Buana University Yogyakarta students in 2023. A purposive sampling approach was utilized in this study, involving the employment of a total of 66 samples. The research methodology applied here is quantitative, involving the use of SPSS Version 26 software for data analysis. Descriptive statistical methods, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing were among the analytical techniques used. The results of this study show that financial literacy has a positive impact on financial management behavior, while lifestyle exerts a negative influence on financial management behavior. Additionally, academic ability was found to have a positive impact on the financial management behavior of students at Mercu Buana University in Yogyakarta in 2023.